2017
DOI: 10.1016/j.watres.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Removal characteristics of DON in pharmaceutical wastewater and its influence on the N-nitrosodimethylamine formation potential and acute toxicity of DOM

Abstract: Previous research has focused on dissolved organic carbon (DOC) as a surrogate for dissolved organic matter (DOM) in pharmaceutical wastewater. Dissolved organic nitrogen (DON) as a part of DOM has received little attention. This study investigated the removal characteristics of DON and its influence on the N-nitrosodimethylamine formation potential (NDMA FP) and acute toxicity of DOM in a full-scale hydrolysis/acidification + anaerobic/anoxic/aerobic + moving bed biofilm reactor (MBBR) process treating pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…This technique is highly sensitive to most toxicants in a short running time. And that, the enzyme action and the chemical condition in the test are also similar to that in many higher mammals (4,5).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This technique is highly sensitive to most toxicants in a short running time. And that, the enzyme action and the chemical condition in the test are also similar to that in many higher mammals (4,5).…”
Section: Introductionsupporting
confidence: 58%
“…There is a primary fact that most natural processes are controlled by the interactions of numerous factors. Some typical examples are the reaction effects caused by the complex relationships, such as environment pollutions (4,5), health risk assessment (6), catalytic effects (7), toxicity (8), etc. Therefore, the exploration of these complex relationships plays a decisive role in accurately grasping many natural laws in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research has indicated that the NDMA precursors include the inorganic compounds (such as N 2 O 3 , NH 2 Cl, NHCl 2 , hydroxylamine, etc.) and a range of organic compounds [57,[84][85][86][87][88][89].…”
Section: Precursorsmentioning
confidence: 99%
“…NDMA precursors are predominantly found in DON sources [102,[107][108][109][110]. NDMA formation is correlated with the ratio of DOC to DON (DOC/DON) [89,105]. In general, the generation of NDMA is inversely proportional to the ratio.…”
Section: Organic Nitrogenmentioning
confidence: 99%
“…Lin et al [6] researched six lakes, including Poyang Lake, and Dongting Lake in Hunan and Jiangxi Provinces, China, and reported that the DON content varied from 17.18 mg/kg to 292.31 mg/kg (mean content, 134.45 mg/kg), comprising 51.86% TDN and 7.14% total nitrogen (TN) across the six lakes; in addition, the distribution of DON was closely related to pollution levels in each lake. The sources of DON are extensive, including sediment, organic matter in the soil, microbial and biological organic debris, and their metabolites [7], besides, the effluent discharged from wastewater treatment plants is also an important source of anthropogenic DON loading to surface waters [8,9], with extremely complex composition [10] that can be bioavailable to aquatic plant species and toxic risk [11].…”
Section: Introductionmentioning
confidence: 99%